Substituent effect on the electronic, structural, spectroscopic (IR and NMR) properties of H-C@Al12-Para-C6H4X clusters: A DFT outlook - Reza Ghiasi; Rose Tale; Vahid Daneshdoost (Results in Chemistry, 2025)
Substituent effect on the electronic, structural, spectroscopic (IR and NMR) properties of H-C@Al12-para-C6H4X clusters was explored at CAM-B3LYP/6-311G(d,p) level of theory. Selected substitutions were NH2, OH, Me, H, Cl, SiH3, CN, NC, NO2. Vertical ionization potential and vertical electron affinity of these molecules were computed. Frontier orbitals energy values and HOMO-LUMO gap of these clusters were evaluated. Substituent effect on the Al-CPh and AlH bond distances were indicated. These computed parameters revealed good linear correlations with Hammett's constants. Dipole moment, polarizability and first hyperpolarizability values were reported. Electronic effect of substituents on the chemical shift values of bonded C and H atoms to Al were illustrated. Most intensity vibrational mode of the studied cluster was determined.